Pain and disease according to integral anthroposophical dentistry - Célia Regina Lulo Galitesi; Flaviana Bombarda de Andrade; Ana Flávia Sanches Borges (Sociedade Brasileira de Pesquisa Odontológica, 2012)
From an academic standpoint, the university format, in general, has been nurturing a "paradigm of expertise" and, consequently, the relationship between specialties has declined. The upshot is that recent college dental graduates have adopted a clinical performance focusing on system parts and their specificities, in detriment to a more comprehensive view of the mouth and of the patient as a whole, with his/her vital, emotional and individual attributes. An interaction between the several different areas of human knowledge is needed imminently to decrease the dichotomy in professional behavior, because the demand for professionals and dental patients interested in a more comprehensive approach are increasing day by day. Patients want to know: "What, in fact, is behind the etiological extrinsic and intrinsic factors that maintain neuropathic pain, recurrent thrush, or persistent halitosis," among other questions, "even under the care of a dentist?" or "Why is this disease affecting me?" There are several issues composing the paradigm of salutogenesis: What are the essential aspects that constitute a healthy individual, overlapping the usual investigation: How to destroy, avoid and quell the pathological agents? A proposed approach is based on salutogenesis, which examines such issues. According to this approach, anthroposophical dentistry includes determinant factors, determinants of health, basic research and the development of oral health promotion, thus connecting dental academia with integrative thinking, while also complementing and gathering information that subsidizes basic research with the primordial concepts on laws governing the parameters involved in the vital processes of nature.